Impaired Maintenance of Interpersonal Synchronization in Musical Improvisations of Patients with Borderline Personality Disorder - Foubert, Katrien; Collins, Tom; De Backer, Jos (Frontiers in Psychology, 2017)
Borderline personality disorder (BPD) is a serious and complex mental disorder with a lifetime prevalence of 5.9%, characterized by pervasive difficulties with emotion regulation, impulse control, and instability in interpersonal relationships and self-image. Impairments in interpersonal functioning have always been a prominent characteristic of BPD, indicating a need for research to identify the specific interpersonal processes that are problematic for diagnosed individuals. Previous research has concentrated on self-report questionnaires, unidirectional tests, and experimental paradigms wherein the exchange of social signals between individuals was not the focus. We propose joint musical improvisation as an alternative method to investigate interpersonal processes. Using a novel, carefully planned, ABA' accompaniment paradigm, and taking into account the possible influences of mood, psychotropic medication, general attachment, and musical sophistication, we recorded piano improvisations of 16 BPD patients and 12 matched healthy controls. We hypothesized that the insecure attachment system associated with BPD would be activated in the joint improvisation and manifest in measures of timing behavior. Results indicated that a logistic regression model, built on differences in timing deviations, predicted diagnosis with 82% success. More specifically, over the course of the improvisation B section (freer improvisation), controls’ timing deviations decreased (temporal synchrony became more precise) whereas that of the patients with BPD did not, confirming our hypothesis. These findings are in accordance with previous research, where BPD is characterized by difficulties in attachment relationships such as maintaining strong attachment with others, but it is novel to find empirical evidence of such issues in joint musical improvisation. We suggest further longitudinal research within the field of music therapy, to study how recovery of these timing habits are related to attachment experiences and interpersonal functioning in general.